The transformative role of peer learning projects in 21st century schools: achievements from five Portuguese educational institutions - Carvalho, Ana Raquel (2021)
Rethinking the role of education in the 21st century implies acknowledging the power of learning and the urgency of making learning provision more meaningful, inclusive, and student-centred, which assumes particular importance when learner disengagement is still a global issue in elementary and secondary education. Rooted in social constructivism principles, peer learning is a learner-centred approach that facilitates the development of soft and technical skills, with evidence-based contributions to learners’ academic performance under the cognitive, affective, and social dimensions. This study aims to find evidence of the transformative role of peer learning projects in four Portuguese secondary schools and a higher education institution through teachers and peer teacher students’ (PTS) perceptions of these projects’ purpose, implementation, and impact on the educational community, particularly on PTS. Data were collected by means of a semi-structured in-depth interview and a survey by questionnaire, and content analysis and descriptive statistics were the techniques used. Results show cooperation and interpersonal skills’ improvement as major strengths of these projects, whereas the challenges are mostly organisational, e.g., reduced teacher service time and coordination of learners’ schedules. Conclusions highlight the potential of peer learning projects to promote pedagogical transformation and innovation in 21st century schools.